REVOLUTIONIZING BUSINESS MANAGEMENT: STRATEGIC HR OPTIMIZATION FOR SUSTAINABLE PROFITABILITY IN INDONESIA'S TECHNOLOGICAL LANDSCAPE - Kosasih Kosasih; Farida Yuliaty; Megandhi Gusti Wardhana; Vip Paramarta, Sobarna Kartamihardja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Indonesia's technological landscape is in a state of constant evolution, offering both unprecedented opportunities and formidable challenges to businesses. Strategic Human Resource (HR) optimization has emerged as a critical imperative to thrive in this dynamic environment. This research delves into the pivotal role of HR management in achieving sustainable profitability within the Indonesian technological landscape. The study employs a mixed-method approach, combining quantitative data from surveys and interviews with HR professionals, business leaders, and employees and qualitative data from industry reports and case studies. The findings underscore the importance of strategic HR optimization, revealing four key aspects: the role of HR in technological transformation, addressing the skills gap, promoting diversity and inclusion, and prioritizing employee engagement and well-being. In-depth analysis demonstrates that HR departments are crucial in guiding organizations through digital transformation. Aligning HR strategies with technology adoption leads to higher success rates and reduced resistance to change. Furthermore, a significant skills gap in the workforce demands substantial investment in training and development programs. Embracing diversity and inclusion fosters innovation and competitiveness  while  prioritizing  employee  engagement  and  well-being increases productivity and profitability. This research provides practical insights for businesses operating in Indonesia's ever-changing technological landscape. By implementing the strategies and recommendations presented, organizations can revolutionize their business management, positioning themselves as leaders in this dynamic environment ensuring long-term success and profitability.